“We Copy to Join in, to Not Be Lonely”: Adolescents in Special Education Reflect on Using Dramatic Imitation in Group Dramatherapy to Enhance Relational Connection and Belonging - Musicka-Williams, Amanda (Frontiers in Psychology, 2020)
This paper focuses on key findings from doctoral research which explored relationships and interpersonal learning through group dramatherapy and creative interviewing with adolescents in special education. A constructivist grounded theory study, positioning adolescents diagnosed with intellectual/developmental disabilities as the experts of their own relational experiences, revealed their self- identified tendency to “copy others”. Within the final co-created grounded theory “copying” was presented and discussed as a tool which participants consciously employed “to play with”, “learn from” and experience relational connection to other people. Participants further communicated a common experience of being socially ostracized and reflected an awareness that their tendency to “copy others” was underpinned by the need to belong. Connection to others and an experience of belonging was therefore expressed as the ultimate therapeutic experience that participants wanted to have within group dramatherapy. Participant responses which link dramatic imitation to a self-identified tendency “to copy”, are discussed with regards to how imitation provides an accessible point of dramatic entry from which adolescents in special education can begin to imaginatively explore new ways of being and inter-relating. Recommendations for how dramatherapists might centralize imitative aspects of the dramatic process to achieve therapeutic intent, when working alongside adolescents with intellectual/ developmental disabilities are discussed with specific focus on achieving the ultimate therapeutic goal; creating a space of belonging for young people who are not having this basic human need met in wider social circumstances.